(untitled) (Research, Society and Development, 2024)
Parkinson’s disease is a neurodegenerative disorder associated mainly with older age, and one of its comorbidities is parkinsonian dementia. One of the current alternatives for treating this dementia is the use of acetylcholinesterase inhibitors (AChEs), which have the potential to improve dementia symptoms. This study aims to present, through an integrative review, the efficacy of AChEs for the treatment of dementia caused by Parkinson’s disease, which affects patients’ quality of life. The results show that early and continuous initiation of AChE therapy improves psychotic symptoms, especially delusions and hallucinations. Thus, the study concludes that AChE therapy is promising and that further studies are needed to assess long-term outcomes and consolidate the findings of this article.